Comparison of Acellular Solutions for Ex-situ Perfusion of Amputated Limbs. Issue 11 (30th December 2020) - Haug, Valentin; Kollar, Branislav; Endo, Yori; Kadakia, Nikita; Veeramani, Anamika; Kauke, Martin; Tchiloemba, Bianief; Klasek, Robin; Pomahac, Bohdan
Abstract: Introduction: Hypothermic ex-situ machine perfusion (MP) has been shown to be a promising alternative to static cold storage (SCS) for preservation of solid organs for transplantation and vascularized composite allotransplantation. Perfusion with blood-based perfusion solutions in austere environments is problematic due to their need for appropriate storage and short shelf life, making it impractical for military and emergency use. Acellular perfusion has been shown to be effective, but the ideal perfusate solution for MP of amputated limbs is yet to be determined. The purpose of this study is to evaluate the efficacy of alternative perfusate solutions, such as dextran-enriched Phoxilium, Steen, and Phoxilium in ex-vivo hypothermic MP of amputated limbs in a porcine model. Materials and methods: Amputated forelimbs from Yorkshire pigs ( n = 8) were preserved either in SCS ( n = 2) at 4°C for 12 hours or machine-perfused at 10°C for 12 hours with oxygenated perfusion solutions ( n = 6) at a constant flow rate. The perfusates used include modified Steen-solution, Phoxilium (PHOX), or Phoxilium enriched with dextran-40 (PHODEX). The perfusate was exchanged after 1 and 6 hours of perfusion. Machine data were recorded continuously. Perfusate samples for clinical chemistry, blood gas analysis, and muscle biopsies were procured at specific timepoints and subsequently analyzed. In this semi in-vivo study, limb replantation has not been performed. Results: After amputation, every limb was successfully transferred and connected to our perfusion device. The mean total ischemia time was 77.5 ± 5.24 minutes. The temperature of the perfusion solution was maintained at 10.18 ± 2.01°C, and perfusion pressure at 24.48 ± 10.72 mmHg. Limb weight increased by 3% in the SCS group, 36% in the PHODEX group, 25% in the Steen group, and 58% in the PHOX group after 12 hours. This increase was significant in the PHOX group compared with the SCS group. All perfusion groups showed a pressure increase of 10.99 mmHg over time due to edema. The levels of HIF-1a decreased over time in all groups except the Steen and the PHODEX group. The biomarkers of muscle injury in the perfusate samples, such as creatine kinase and lactate-dehydrogenase, showed a significant difference between groups, with highest values in the PHODEX group. No significant differences were found in the results of the blood gas analysis. Conclusion: With the exception of significantly higher levels of creatine kinase and lactate dehydrogenase, MP with dextran-enriched Phoxilium provides similar results as that of the commercially available perfusates such as Steen, without the need for cold storage, and at circa 5% of the cost of the Steen solution. Further large-scale replantation studies are necessary to evaluate the efficacy of dextran-enriched Phoxilium as an alternate perfusate solution.